Magnetic resonance elastography for prediction of long‐term progression and outcome in chronic liver disease: A retrospective study - Gidener, Tolga; Yin, Meng; Dierkhising, Ross A.; Allen, Alina M.; Ehman, Richard L.; Venkatesh, Sudhakar K. (Hepatology (Baltimore, Md.), 2022)
Background and Aims Although magnetic resonance elastography (MRE) has been well‐established for detecting and staging liver fibrosis, its prognostic role in determining outcomes of chronic liver disease (CLD) is mostly unknown. Approach and Results This retrospective study consisted of 1269 subjects who underwent MRE between 2007 and 2009 and followed up until death or last known clinical encounter or end of study period. Charts were reviewed for cirrhosis development, decompensation, and transplant or death. The cohort was split into baseline noncirrhosis (group 1), compensated cirrhosis (group 2), and decompensated cirrhosis (group 3). Cox‐regression analysis with age, sex, splenomegaly, CLD etiology, Child‐Pugh Score (CPS), Fibrosis‐4 Index (FIB‐4) score, and Model for End‐Stage Liver Disease (MELD)–adjusted HR for every 1‐kPa increase in liver stiffness measurement (LSM) were used to assess the predictive performance of MRE on outcomes. Group 1 (n = 821) had baseline median LSM of 2.8 kPa, and cirrhosis developed in 72 (8.8%) subjects with an overall rate of about 1% cirrhosis/year. Baseline LSM predicted the future cirrhosis with multivariable adjusted HR of 2.38 (p < 0.0001) (concordance, 0.84). In group 2 (n = 277) with baseline median LSM of 5.7 kPa, 83 (30%) subjects developed decompensation. Baseline LSM predicted the future decompensation in cirrhosis with FIB‐4 and MELD‐adjusted HR of 1.22 (p < 0.0001) (concordance, 0.75). In group 3 (n = 171) with median baseline LSM of 6.8 kPa (5.2, 8.4), 113 (66%) subjects had either death or transplant. Baseline LSM predicted the future transplant or death with HR of 1.11 (p = 0.013) (concordance 0.53) but not in CPS and MELD‐adjusted models (p = 0.08). Conclusion MRE‐based LSM is independently predictive of development of future cirrhosis and decompensation, and has predictive value in future transplant/death in patients with CLD.